Analisis Akuntansi Pendapatan Proyek Konstruksi Perumahan Berbasis PSAK NO. 72 Pada PT. Randu Putra Perkasa Nusantara Kota Probolinggo - Rusti, Mutimmah; Novadiani Haidiputri, Trivosa Aprilia; Lidyana, Novita; Ningsih, Ira Ferdiana (Ecobuss, 2021)
This study aims to determine the implementation of PSAK No. 72 on income from housing construction projects at PT. Randu Putra Perkasa Nusantara. The method used is a qualitative method. Data Collection techniques in the form of direct observation, interviewing informants, literature studies, and documentation. The results of the study show the implementation of income from PT. Randu Putra Perkasa Nusantara has not fully complied with the implementation of PSAK No. 72. Companies in identifying contracts need to reassess the ability of customers to pay, because many customers in the in-house system pay more than the payment deadline. The company’s revenue recognition needs to be reevaluated, because according to PSAK No. 72 revenues are received after completion of all right and obligations of the company and 100% handover to customers. Revenue recognition all the time, the company has not met one of the 3 criteria for revenue recognition all the time. Regarding disclosure, the company has not made catatan atas laporan keuangan (CALK).